Revisiting the "compliance-vs.-rebalancing" debate in WTO scholarship: Towards a unified research agenda - Simon A. B. Schropp (Graduate Institute of International Studies, 2007)
This paper constitutes an attempt to reframe and eventually deflate the ongoing 'compliance-vs.-rebalancing' debate which has permeated WTO scholarship for the last 10 years. Our main criticism concerns the substance of the entire debate. We find that scholars on both sides of the compliance/rebalancing controversy put an unduly rigid emphasis on the subsequent issues of WTO enforcement and the interpretation of the wording of the dispute settlement understanding. They thereby neglected systemic issues of contracting, viz. the nature of contractual entitlements, the need for trade policy flexibility mechanisms and the optimal design of the appropriate remedies. We redefine and recalibrate the compliance/rebalancing controversy along the lines of the nature of the WTO contract. This results in to three key findings: First, none of the two schools of thought succeeds in giving an accurate picture of the WTO treaty. Second, the two perspectives actually portray two strikingly different concepts of the WTO contract, and therefore have been at cross-purposes from the very beginning. This implies a third finding: The two schools of thought essentially describe different facets of the same complex WTO contract. Hence, they have hardly been at loggerheads at all, and are actually complementing each other in important aspects. We lay out a unified research agenda that practitioners, economists, trade lawyers, and international relations scholars alike can accept. The agenda may contribute to reconciling the two opposing views and help WTO scholarship tackle the real systemic issues of the WTO Agreement.
Keywords: F02; F13; F51; F53; F55; K33; K42; 330; WTO; dispute settlement; incomplete contracts; remedies; enforcement; WTO-Regeln; Handelsabkommen; Unvollständiger Vertrag; Rechtsdurchsetzung; Handelskonflikt; Internationale Schiedsgerichtsbarkeit; Theorie